The enigmatic dollar-euro exchange rate and the world's biggest forex market: Performance, causes, consequences - Jan Priewe (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2016)
Foreign exchange markets are the biggest financial markets on the globe, the dollar-euro market is the biggest among them with a daily turnover of 1.3 trillion. This market is the interface of the euro bloc and the dollar bloc which use mainly one of the major currencies, comprising 45-60% and 25% of global GDP, respectively. Hence the dollar-euro exchange rate is the prime exchange rate among thousands of others. After reviewing the exchange rate performance and the dismal state of exchange rate theories, the paper analyses in the first part the following questions: what determines the large and long swings and the turning points of the exchange rate super-cycle; what is the role of "fundamentals" and what are the non-fundamental determinants of the dollar-euro exchange rate. In the second part we analyse the consequences of high volatility and frequent misalignment of the dollar-euro rate: in what way is this exchange rate relevant for the real economies, as both the majority of the euro area's and the trade of the U.S. is denominated in own currency; what are the interdependencies between the dollar-euro exchange rate and internal imbalances in the current accounts of the euro area; has the relationship between exchange rates and trade changed, due to reduced elasticities; what is the impact of dollar-euro exchange rate on international financial markets. – – Devisenmärkte sind die größten Finanzmärkte der Welt, und unter ihnen ist der Dollar-Euro Markt der größte mit einem täglichen Transaktionsvolumen von 1.3 Billionen US-Dollar. Dieser Markt ist die Schnittstelle zwischen den beiden großen Währungsblöcken, die rund 45-60% des Welt-BIP für den Dollar-Block und etwa 25% für den Euro-Block ausmachen. Unter allen Wechselkurse der Weltwirtschaft ist der Dollar-Euro-Kurs der wichtigste. Nach einem Überblick über die langfristige Wechselkursentwicklung und über den Stand der Wechselkurstheorie werden im ersten Teil die folgenden Fragen untersucht: was bestimmt die großen Wechselkursausschläge nach oben und unten, und hier insbesondere die Umkehrpunkte im Rahmen des Super-Zyklus der Wechselkursdynamik; welche Rolle spielen dabei "Fundamentalfaktoren" sowie nicht-fundamentale Determinanten. Im zweiten Teil wird nach den Folgen des volatilen und überwiegend ungleichgewichtigen Wechselkurses für die Realwirtschaft gefragt: welche Relevanz hat der Dollar-Euro Wechselkurs für den Warenhandel beider Währungsblöcke, wenn man berücksichtigt, dass Exporte und Importe beider Währungsblöcke in großem Maße in eigener Währung fakturiert werden; gibt es Wechselwirkungen zwischen dem Wechselkurs und den Leistungsbilanzungleichgewichten in der europäischen Währungsunion; hat sich das Verhältnis von Wechselkurs und Handel im Laufe der Globalisierung aufgrund veränderter Elastizitäten gelockert; wie beeinflusst der Wechselkurs internationale Finanzmärkte.
urn:nbn:de:101:1-201607296818
Keywords: F31; F32; F33; F36; G01; 330; Foreign Exchange; Current Account Adjustment; International Monetary Arrangements; Financial Aspects of Economic Integration; Behavioural Finance